Declines and pronounced state-level variation in clozapine use among Medicare patients - Luke R. Cavanah; Maria Y. Tian; Jessica L. Goldhirsh; Leighton Y. Huey; Brian J. Piper (PLoS ONE, 2025)
Schizophrenia-spectrum disorders are debilitating and contribute to a substantial economic burden. Clinicians have historically underutilized clozapine, an atypical antipsychotic traditionally reserved for treatment-resistant schizophrenia, due to the medication’s adverse effect profile and associated management requirements, concerns of complications from poor treatment adherence, and inadequate training/exposure to its use. In addition to alleviating schizophrenia symptoms when multiple other medications have failed, clozapine has other areas of demonstrated effectiveness, such as reduced suicide ideation and action, aggression, substance use, and all-cause mortality benefits that compel its use. This study aimed to characterize clozapine utilization by United States (US) Medicare patients from 2015 to 2020. Additionally, we identified the states that prescribed significantly different amounts than the national average. We observed a steady decrease in clozapine use adjusted for population (−18.0%) and spending (−24.9%) over time. For all years, there was pronounced geographic heterogeneity (average: nine-fold) in population-corrected clozapine use. Massachusetts (2015−20: 95.4, 82.7, 76.8, 72.2, 71.2, 63.7 prescriptions per thousand enrollees) and South Dakota (2015−20: 78.0, 77.4, 78.4, 75.6, 72.0, 71.6) were the only states that prescribed significantly more than average, and none prescribed significantly less. Clozapine use by US Medicare patients is low, decreasing, and concerning for underutilization—patterns previously identified for US Medicaid recipients. Further study of the reasons for the pronounced state variation is needed. Education interventions, training reform, and devices that ease required routine blood monitoring are all practical solutions to optimize clozapine use.